Female labour supply and childcare in Italy - Edlira Narazani; Francesco Figari (European Commission, Joint Research Centre (JRC), 2017)
It is widely recognized that childcare has important pedagogical, economic and social effects on both children and parents. This paper is the first attempt to estimate a joint structural model of female labour supply and childcare behavior applied to Italy in order to analyse the effects of relaxing the existing constraints in terms of childcare availability and costs by considering public, private and informal childcare. Results suggest that Italian households might alter their childcare and labour supply behaviors substantially if the coverage rate of formal childcare increases to reach the European targets. Overall, increasing child care coverage is estimated to be more effective in enhancing labor incentives than decreasing existing child care costs, at the same budgetary cost.
Keywords: H53; J13; J22; I38; 330; childcare; female labour supply; Italy